Processing of information from the parafascicular nucleus of the thalamus through the basal ganglia. Issue 6 (31st March 2022) - Hanini‐Daoud, Maroua; Jaouen, Florence; Salin, Pascal; Kerkerian‐Le Goff, Lydia; Maurice, Nicolas
Abstract: Accumulating evidence implicates the parafascicular nucleus of the thalamus (Pf) in basal ganglia (BG)‐related functions and pathologies. Despite Pf connectivity with all BG components, most attention is focused on the thalamostriatal system and an integrated view of thalamic information processing in this network is still lacking. Here, we addressed this question by recording the responses elicited by Pf activation in single neurons of the substantia nigra pars reticulata (SNr), the main BG output structure in rodents, in anesthetized mice. We performed optogenetic activation of Pf neurons innervating the striatum, the subthalamic nucleus (STN), or the SNr using virally mediated transcellular delivery of Cre from injection in either target in Rosa26‐LoxP‐stop‐ChR2‐EYFP mice to drive channelrhodopsin expression. Photoactivation of Pf neurons connecting the striatum evoked an inhibition often followed by an excitation, likely resulting from the activation of the trans‐striatal direct and indirect pathways, respectively. Photoactivation of Pf neurons connecting the SNr or the STN triggered one or two early excitations, suggesting partial functional overlap of trans‐subthalamic and direct thalamonigral projections. Excitations were followed in about half of the cases by an inhibition that might reflect recruitment of intranigral inhibitory loops. Finally, global Pf stimulation, electrical or optogenetic, elicited similar complex responses comprising up to four components: one or two short‐latency excitations, an inhibition, and a late excitation. These data provide evidence for functional connections between the Pf and different BG components and for convergence of the information processed through these pathways in single SNr neurons, stressing their importance in regulating BG outflow. Abstract : Activating subpopulations of parafascicular (Pf) neurons selected on the basis of their projections to different basal ganglia components shows that the activity of the substantia nigra pars reticulata (SNr) can be shaped by convergent information processed through direct thalamonigral (1), trans‐subthalamic (2), and trans‐striatal direct (3) and indirect (4) subcircuits.